Outside-in: Overview of Delivery Method in Sirna Therapy - Yuan, Kaijun (Transactions on Materials, Biotechnology and Life Sciences, 2024)
RNA interference (RNAi) is a Universal biological system based on double-strand small interference RNA (siRNA). RNAi efficiently inhibit the expression of genes based on a guiding strand. SiRNA can be applied against a broad spectrum of diseases but is limited by insufficient siRNA delivery methods. Delivery of siRNA is a challenging direction of modern molecular biology and pharmacy study; scientists aim to improve the efficiency and accuracy of siRNA-based treatment. Many approaches have been suggested to overcome challenges in effectively and safely delivering siRNA to the necessary tissues, cells, and organisms, Furthermore, endeavors have been concentrated on augmenting the effectiveness of siRNA concerning its stability, activity, specificity, and minimizing side effects. This review overviews the barriers to siRNA entrance and the challenge of siRNA delivery vectors, introduces and categorizes the currently available siRNA delivery systems including conjugate-based vectors, Lipid nanoparticle vectors, and Dendrimer vectors. And discuss the latest progress in the development of siRNA therapy. This review aims to offer a concise overview of the present advancements in siRNA delivery research and suggests potential avenues for future exploration.